Information Retrieval Mechanism for Dynamic Health Care - Devi, C. Dharma; Thaddeus, S (International Journal of Computer Sciences and Engineering, 2018)
In spite of the commendable success of Big Data, there are still many challenges with regard to storage, retrieval, analysis and prediction. A framework was proposed for information retrieval by integrating ontology models with Big Data. Evaluation of this framework with different domain models is a invariable work to validate this model. This study applies the framework to health care data and thus identifies the strengths and weaknesses of the framework.